2019
DOI: 10.1038/s41598-019-52153-1
|View full text |Cite
|
Sign up to set email alerts
|

CENP-A binding domains and recombination patterns in horse spermatocytes

Abstract: Centromeres exert an inhibitory effect on meiotic recombination, but the possible contribution of satellite DNA to this “centromere effect” is under debate. In the horse, satellite DNA is present at all centromeres with the exception of the one from chromosome 11. This organization of centromeres allowed us to investigate the role of satellite DNA on recombination suppression in horse spermatocytes at the stage of pachytene. To this aim we analysed the distribution of the MLH1 protein, marker of recombination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 54 publications
(70 reference statements)
0
19
0
Order By: Relevance
“…Although this was consistent with our observations (the proportion of chromosome arms with zero CO was slightly higher in heterozygous Rb fusions than nonfused chromosomes), we also detected a strong reduction of recombination in homozygous Rb-fused chromosomes, mirroring early cytological observations 38 . Decreased recombination in homozygous Rb fusions is counterintuitive but could be explained by the presence of double-centromeric signals that represented misaligned centromeres 39 . Since centromeres can reduce recombination rates (so-called centromere interference 40 ), the presence of double centromeres could magnify this effect, interfering with both the formation of COs during prophase and subsequently affecting chromosome segregation in metaphase I.…”
Section: Discussionmentioning
confidence: 99%
“…Although this was consistent with our observations (the proportion of chromosome arms with zero CO was slightly higher in heterozygous Rb fusions than nonfused chromosomes), we also detected a strong reduction of recombination in homozygous Rb-fused chromosomes, mirroring early cytological observations 38 . Decreased recombination in homozygous Rb fusions is counterintuitive but could be explained by the presence of double-centromeric signals that represented misaligned centromeres 39 . Since centromeres can reduce recombination rates (so-called centromere interference 40 ), the presence of double centromeres could magnify this effect, interfering with both the formation of COs during prophase and subsequently affecting chromosome segregation in metaphase I.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin from primary fibroblasts was cross-linked with 1% formaldehyde, extracted, and sonicated to obtain DNA fragments ranging from 200 to 800 bp. Immunoprecipitation was performed as previously described (Nergadze, et al 2018) by using an anti-CENP-A serum (Cappelletti, et al 2019). Grevy's zebras was performed using an iterative chromosome walking approach based on paired-end ChIPseq reads, as previously described (Nergadze, et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin from primary fibroblasts was cross-linked with 1% formaldehyde, extracted, and sonicated to obtain DNA fragments ranging from 200 to 800 bp. Immunoprecipitation was performed as previously described (Nergadze, et al 2018) by using an anti-CENP-A serum (Cappelletti, et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The position of the ECA11 satellite-less centromere, identified as the CENP-A binding domain, is not fixed in the horse population but slides within an about the 500 kb region, giving rise to different positional alleles or "epialleles" [106,111,112]. The analysis of these epialleles carried out on families composed by horses, donkeys, and their hybrid offspring (mule/hinny) revealed that they are inherited as Mendelian traits, but their position can slide in one generation [106].…”
Section: Unique Aspects Of the Horse Genomementioning
confidence: 99%
“…The absence of satellite DNA at these centromeres also provides a unique opportunity to understand whether some typical features of mammalian centromeres depend on the presence of satellite DNA. In particular, it was possible to demonstrate that satellite DNA was not necessary for segregation fidelity of the centromere [113] and was not implicated in the suppression of meiotic recombination, which is typically exerted by the centromere [112].…”
Section: Unique Aspects Of the Horse Genomementioning
confidence: 99%